2013
DOI: 10.1080/15213269.2012.755877
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Embodied Experiences on Self-Other Merging, Attitude, and Helping Behavior

Abstract: Immersive virtual environment technology (IVET) provides users with vivid sensory information that allow them to embody another person's perceptual experiences. Three experiments explored whether embodied experiences via IVET would elicit greater selfother merging, favorable attitudes, and helping toward persons with disabilities compared to traditional perspective taking, which relies on imagination to put the self in another person's shoes. Trait dispositions to feel concern for others was tested as a modera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
155
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 209 publications
(176 citation statements)
references
References 46 publications
8
155
2
1
Order By: Relevance
“…Although not in the context of discrimination there is some evidence from the work of Ahn et al (2013) that this might be the case. They immersed people with normal vision into an HMD-delivered VR where they experienced certain types of color blindness.…”
Section: Discriminationmentioning
confidence: 93%
“…Although not in the context of discrimination there is some evidence from the work of Ahn et al (2013) that this might be the case. They immersed people with normal vision into an HMD-delivered VR where they experienced certain types of color blindness.…”
Section: Discriminationmentioning
confidence: 93%
“…For instance, few people have direct experience with certain disabilities, so using IVEs to embody the sensory experiences of a disability one has not encountered may be much more powerful than relying on an aschematic imagination. Ahn and colleagues () tested this notion and demonstrated that embodying the experience of a person with a visual disability in a perspective‐taking task using IVEs led to greater helping behavior in the physical world than perspective taking, which relied upon imagining the disability. Another study demonstrated that direct experiences of an opponent simulated through virtual worlds prior to a negotiation task encouraged individuals to develop a positive attitude toward the opponent and make more concessions than indirect experiences (Gehlbach et al, ).…”
Section: Embodying Experiences Of Animals In Immersive Virtual Enviromentioning
confidence: 99%
“…VEs yield potential advantages over traditional frames, particularly in the context of gain and loss frames aiming to modify behaviors. One such advantage is that virtual experiences are more persuasive than messages in print or video presenting comparable amounts of information (Ahn et al, 2013(Ahn et al, , 2014, most likely due to VEs' unique affordances such as simulated sensory information and high interactivity. These affordances seemed to result in the persistent salience of virtual experiences in the mind as vivid experiences, implying that classical stipulations of framing theories, although still applicable, become amplified in VEs and the effects are sustained over time.…”
Section: Gain and Loss Framed Virtual Experiencesmentioning
confidence: 99%